Risk factors for type 2 diabetes mellitus in adolescentes - Wendy Valdés Gómez; Arianna Almirall Sánchez; Miguel Ángel Gutiérrez Pérez (Medisur)
Foundation: The increasing prevalence of diabetes mellitus type 2 (DM2) from the pediatric ages, has made its morbidity and mortality a major public health problem. Early detection of DM2 risk factors in adolescents, would allow preventive actions with a risk approach, which would lead to decrease the incidence of this condition, being a fundamental pillar of primary care Objective: To identify the presence of DM2 risk factors in adolescents. Method: A cross-sectional descriptive study was conducted in a health area ("Raúl Gómez García" Polyclinic) with a sample of 96 adolescents. Variables such as age, sex, history of gestational diabetes, low birth weight, breastfeeding time, family history of DM2, fruit / vegetable intake, physical activity and physical examination results were collected. Results: The 62.50% of the adolescents belonged to the feminine sex and the early adolescence. The inadequate consumption of fruits and vegetables with 81.25% was the most common risk factor, followed by a sedentary lifestyle with 45.83%. All adolescents had at least one risk factor, and 72.92% had 3 or more with a predominance in females (p = 0.022). Conclusion: There is a high frequency of risk factors for developing of DM2 in adolescents, with a predominance of modifiable factors. Most adolescents had an increased metabolic risk when presenting 3 or more risk factors, especially females.